The vulnerability of both genders in HIV and AIDS narratives: a study of Lutanga Shaba’s Secrets of a Woman’s Soul (2006), The Haunted Trail by Philip Chidavaenzi (2012) and Valerie Tagwira’s The Uncertainty of Hope (2006) - Dhlula, Nonceba Wendy (Midlands State University, 2018)
This research examines the vulnerability of both genders in HIV and AIDS narratives focusing on Lutanga Shaba’s Secrets of a Woman’s Soul (2006), The Haunted Trail by Philip Chidavaenzi (2012) and Valerie Tagwira’s The Uncertainty of Hope (2006). The novels speak expansively on the issues instigated by societal expectations and the stigmatization in the context of HIV and AIDS. The thesis also focuses factors that influence the vulnerability of both men and women during a time where AIDS was a considered a death certificate